An investigation into appreciation used in book reviews in english - Nguyễn Đào Bích Ty (2015)
Book reviews belong to a kind of academic discourse. It is multi-functional, not only providing an information service for the readers and but also an opportunity for reviewers to express their personal opinion of a published book. Basically, book reviews usually contain numerous evaluation resources which require the reviewers and the readers linguistic knowledge and skills to perform the reviewing and comprehending. This study examined the employment of expression of appreciation in English book reviews. All these texts were analyzed quantitatively and qualitatively. Moreover, the descriptive method was employed in doing this research. The study was conducted and based on a descriptive framework of traditional grammar, appraisal and speech act theory. By selecting 134 book reviews in English from some famous websites, the author of this study made a small corpus. The samples of appreciation are instances of words, phrases, and few small clauses identified in the light of the sub-categories of appreciation. The results reveal that adjective phrase is the highly used evaluative resource and has attributive or predicative functions in sentences. Significantly, the construction with pattern: “S + V + CsAPPRECIATION + A” is found very common in appreciation used in EBRs. Similarly, the kind of appreciation used the most was valuation followed by composition and reaction. The present study also investigated the ways in which the writer constructs an evaluative stance in EBRs by employing illocutionary force and boosters in attempt to interact with readers. Finally, the findings also aim at suggesting some implications for comprehending and using appreciation in book reviews as well as teaching English to Vietnamese learners, especially who are interested in the appraisal theory and the writing skill